The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1186/1754-6834-5-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic acids on the growth and lipid accumulation of oleaginous yeast Trichosporon fermentans

Abstract: BackgroundMicrobial lipids have drawn increasing attention in recent years as promising raw materials for biodiesel production, and the use of lignocellulosic hydrolysates as carbon sources seems to be a feasible strategy for cost-effective lipid fermentation with oleaginous microorganisms on a large scale. During the hydrolysis of lignocellulosic materials with dilute acid, however, various kinds of inhibitors, especially large amounts of organic acids, will be produced, which substantially decrease the ferme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 37 publications
6
59
1
Order By: Relevance
“…The authors are not aware of a comparable published study. There have been reports of the effects of selected inhibitors on growth and lipid production by selected yeast species, such as the effect of several inhibitors on Rhodosporidium toruloides [13], aldehydes and organic acids on Trichosporon fermentans [16,17] several inhibitors on Cryptococcus curvatus [50], and screening of the effect of several inhibitors on growth and lipid production by five oleaginous yeast species: R. glutinis, T. cutaneum, R. rubra, R. toruloides, and L. starkeyi [6]. These studies demonstrated that in addition to inhibiting growth, presence of inhibitors correlated with decreased cellular lipid content.…”
Section: Discussionmentioning
confidence: 99%
“…The authors are not aware of a comparable published study. There have been reports of the effects of selected inhibitors on growth and lipid production by selected yeast species, such as the effect of several inhibitors on Rhodosporidium toruloides [13], aldehydes and organic acids on Trichosporon fermentans [16,17] several inhibitors on Cryptococcus curvatus [50], and screening of the effect of several inhibitors on growth and lipid production by five oleaginous yeast species: R. glutinis, T. cutaneum, R. rubra, R. toruloides, and L. starkeyi [6]. These studies demonstrated that in addition to inhibiting growth, presence of inhibitors correlated with decreased cellular lipid content.…”
Section: Discussionmentioning
confidence: 99%
“…Their detoxification strategy involving extraction with ethyl acetate followed by hydrolysis and detoxification with activated carbon became the basic scheme of detoxification for many studies after that. Fermentation of sugar-based substrates, such as glucose, sucrose, fructose, lactose, whey, and xylose have been widely studied; however, research on lipid production from organic acids is still very limited [26,28,53,70]. In another study, Lian et al [100] investigated the fermentation of carboxylic acid present in the aqueous fraction of pyrolysis oil as a fermentation substrate for oleaginous yeasts to produce lipids.…”
Section: Indirect Fermentation Of Pyrolytic Sugarsmentioning
confidence: 97%
“…Although there have been many works investigating the inhibitory effect of acetic acid on ethanologenic yeasts under anaerobic conditions (Pampulha et al 1989;Bellissimi et al 2009;Casey et al 2010), so far only a few reports have referred to the effect of acetic acid on oleaginous microorganisms under aerobic conditions (Chen et al 2009;Hu et al 2009;Huang et al 2012). Therefore, little is known about this acid's inhibitory mechanism.…”
Section: Introductionmentioning
confidence: 99%